Efektivitas Penyampaian Informasi Keluhan Pelanggan Melalui Media Sosial PT PLN (Persero) - Mursib Mursib; Abdul Sadad (Journal of Research and Development on Public Policy, 2024)
The purpose of conducting this research is to measure the level of effectiveness in conveying information about PT customer complaints. PLN (Persero) via social media and comparing it with the use of the PLN Mobile application. The use of social media is now important for state agencies to make it easier to provide services to the public, public services using social media as an intermediary according to Law of the Republic of Indonesia No. 11 of 2008 which explains about Electronic Information and Transactions, Article 4 Point (c) explained in detail that, "The use of information technology and electronic transactions is carried out with the aim of increasing the effectiveness and efficiency of public services. The data collection process uses crawling techniques, namely taking data from social media applications and online forms and then processing the data using Netiltyc and SPSS. Meanwhile, analysis techniques data is TNA (Textual Network Analysis), which is an analysis technique that uses text on the internet to process it into visual data and Frequency analysis which analyzes the frequency of occurrence of an indicator.